Calidad de servicio y satisfacción de los clientes de la pollería El Caribeño Iquitos 2024 - Morey Rodriguez, Anggie Daylihgt (2025)
This study was responsible for determining the relational aspect between Service Quality and Customer Satisfaction at Pollería el Caribeño, Iquitos 2024; employing a quantitative descriptive design that avoids experimental methods, to observe and describe the variables without manipulation. The Pearson correlation is 0.724**, with sig. = 0.000**, which is statistically significant. This allows us to accept the hypothesis of the relational existence between the examined variables.